Determinar la correlación entre problemas respiratorios y colapso maxilar en pacientes que acuden a la consulta de ortodoncia en el Hospital Provincial General Docente Riobamba en el periodo septiembre del 2016 - agosto 2017 - Cartagena Aguayo, Jessica Carolina (2018)
The present research work entitled "the correlation between respiratory problems and maxillary collapse in patients attending the orthodontic clinic in the Hospital Provincial General Docente de Riobamba in the Period August 2016-September 2017" aimed to determine the correlation between respiratory problems and maxillary collapse by observation and antero-posterior cephalometric tracings of Ricketts. A sample of 91 anteroposterior radiographs was obtained, which met the inclusion and exclusion criteria proposed. In conclusion it can be determined that in 78% of the population if there was a correlation between respiratory problems and maxillary collapse, especially with patients who had mixed breathing, a frequency of 30% was found due to a bad habit